Experimental and numerical study of biomass fast pyrolysis oil spray combustion: Advanced laser diagnostics and emission spectrometry. (15th September 2019) - Tóth, Pál; Brackmann, Christian; Ögren, Yngve; Mannazhi, Manu Naduvil; Simonsson, Johan; Sepman, Alexey; Bengtsson, Per-Erik; Wiinikka, Henrik
Abstract: The objective of this work was to move towards developing a comprehensible Computational Fluid Dynamics (CFD) model to facilitate the predictive modeling of Fast Pyrolysis Oil (FPO) spray combustion. A CFD model was implemented from the literature and results were compared to 2D data from non-intrusive optical diagnostics involving Planar Laser Induced Fluorescence of the OH radical, Mie scattering imaging and two-color pyrometry using a laboratory-scale, CH4 /air flat-flame with an air-assist atomizer. Furthermore, flame radiation and contributions from graybody sources, chemiluminescence and soot were studied experimentally using emission spectroscopy and Laser Induced Incandescence (LII). Reasonable qualitative agreement was found between experimental and model results in terms of flame structure and temperature. Emission spectroscopy and LII results revealed and confirmed earlier observations regarding the low soot concentration of FPO spray flames; furthermore, it was shown that a significant portion of flame radiation originated from graybody char radiation and chemiluminescence from the Na-content of the FPO. These suggest that the treatment of soot formation might not be important in future computational models; however, the description of char formation and Na chemiluminescence will be important for accurately predicting temperature and radiation profiles, important from the point of e.g., large-scale power applications. Confirmed low soot concentrations are promising from an environmental point of view.